Influence of acute heat mitigation strategies on core temperature, heart rate and aerobic performance in females: A systematic literature review - Convit, L.; Kelly, M. K.; Jardine, W. T.; Périard, J. D.; Carr, A. J.; Warmington, S.; Bowe, S. J.; Snipe, R. M. (Journal of Sports Sciences, 2024)
This review examined the effect of acute heat mitigation strategies on physiological strain and exercise performance in females exercising in the heat. Three databases were searched for original research with an acute heat mitigation (intervention) and control strategy in active females and reporting core temperature, heart rate and/or aerobic exercise performance/capacity with = 24°C wet bulb globe temperature. Hedges` g effect sizes were calculated to evaluate outcomes. Thirteen studies (n = 118) were included. Most studies that applied an acute heat mitigation strategy to females did not reduce thermal (9/10) or cardiovascular (6/6) strain or improve exercise performance/capacity (8/10). The most effective strategies for attenuating thermal strain were pre-cooling with ice-slurry (effect size = -2.2 [95% CI, -3.2, -1.1]) and ice-vests (-1.9 [-2.7, -1.1]), and pre- and per-cooling with an ice-vest (-1.8 [-2.9, -0.7]). Only pre-cooling with an ice-vest improved running performance (-1.8 [-2.9, -0.7]; ~0.43 min) whilst sodium hyperhydration improved cycling capacity at 70% V O2peak (0.8 [0.0, 1.6]; ~20.1 min). There is currently limited research on acute heat mitigation strategies in females, so the evidence for the efficacy is scarce. Some studies show beneficial effects with ice-slurry, ice-vests and sodium hyperhydration, which can guide future research to support female exercise performance in the heat.